Лазерный датчик вибраций, основанный на частотно-фазовом методе измерения расстояний - Брагинец, И.А.; Зайцев, Е.А.; Кононенко, А.Г.; Масюренко, Ю.А.; Ниженский, А.Д. (Технічна електродинаміка, 2011)
In this article the capability of laser vibration sensors based on the frequency-phase method of distance measurement is considered. In such systems the frequency of output quantity is proportional to measuring distance. The vibrations of test object result in phase modulation of this quantity. The article deals with block diagram of frequency-phase vibration sensor. The main feature of device is the absence of reference channel in the circuit. In the proposed vibration sensor as in any frequency-phase distance-measuring system the evaluation of the frequency of its output signal by continuous step change of modulation frequency is made. In this case there is a slight frequency modulation of test signal caused by controlled object's vibrations. At the same time the adequate increment of phase shift through the vibrations is substantially smaller than a measuring phase shift. The expressions for cumulative phase shift considering the vibrations of test object and for output signal of the system are presented. The processing algorithm of output system signal and two reference quadrature voltages is proposed and enables to select the component from the output signal that is proportional to VB parameters.